Pengaruh Literasi Keuangan dan Penggunaan Digitalisasi Keuangan Terhadap Perilaku Keuangan pada Mahasiswa Program Studi Manajemen Angkatan 2021 Universitas Buana Perjuangan Karawang - Viona Marsela; Wanta; Dwi Epty Hidayaty (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Over time, rapid digitalization, financial understanding and financial behavior have become crucial aspects in financial management for the community, especially students. The purpose of this study is to examine the impact of financial literacy skills and the use of financial digitalization on the financial behavior of students in the management study program at Buana Perjuang University, Karawang 2021. This study uses a quantitative method with a verification approach. The analytical technique used is path analysis, with a sample size of 203 students, which examines how the influence of financial literacy and the use of financial digitalization affects students' financial behavior. The results of this study indicate that there is a low relationship between the financial literacy variable and the use of financial digitalization. There is a positive and significant partial effect of the financial literacy variable on the financial behavior variable, and there is also a positive and significant partial effect of the use of financial digitalization on the financial behavior variable but it is relatively low. There is a positive and significant influence simultaneously on the variables of financial literacy and the use of financial digitalization on the financial behavior of students of the Management Study Program, Universitas Buana Perjuangan Karawang, Class of 2021. The implications of this study indicate that increasing financial literacy and utilizing financial digitalization can encourage the formation of wiser, more planned, and more responsible financial behavior of students, with an increase in the number of students who pay their UKT on time.